2014
DOI: 10.1523/jneurosci.2027-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Early Alzheimer's Disease Neuropathology Detected by Proton MR Spectroscopy

Abstract: Proton magnetic resonance spectroscopy ( 1 H-MRS) is sensitive to early neurodegenerative processes associated with Alzheimer's disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 51 publications
(28 reference statements)
13
114
1
Order By: Relevance
“…3). In particular, the tNAA/mIns ratio was significantly lower in these areas in affected subjects compared to healthy controls and suggests neurodegenerative changes [8,51]. Importantly, we also observed that the levels of NAA, mIns, and Glu depend on diagnostic categories as defined by El Escorial criteria (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…3). In particular, the tNAA/mIns ratio was significantly lower in these areas in affected subjects compared to healthy controls and suggests neurodegenerative changes [8,51]. Importantly, we also observed that the levels of NAA, mIns, and Glu depend on diagnostic categories as defined by El Escorial criteria (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…By contrast, SUVr in the striatum and thalamus of Tg mice was significantly elevated at age 3.5 mo and progressively elevated thereafter. These findings are consistent with previous functional MRI studies of brain regions vulnerable to AD [17,18,19] and imply that the entorhinal cortex and hippocampus can be target sites for AD detection via glucose metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…The hippocampus was selected because it is closely related with learning and memory formation and its damage is thought to vitally involve the AD process. Also, studies have shown that the hippocampus is an initial site of Aβ accumulation and neuronal damage [19,34], offering a pathologic basis for AD-related cognitive deficits. Once hippocampal damage reaches a certain level, resulting learning and memory deficits can be evaluated by the MWM in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Results were comparable in models that did not include fCSF volume as a covariate. NAA is typically diminished in AD,17, 18 and this pattern held for this study ( F [2,75] = 7.231, P = 0.001; NAA was lower in the AD than in the younger CN ( P = 0.0003) and older CN groups ( P = 0.022). Metabolite ratios in the normal groups were consistent with those reported earlier in ProFit literature 24.…”
Section: Resultssupporting
confidence: 76%
“…Proton Magnetic Resonance Spectroscopy ( 1 H‐MRS) provides accurate noninvasive in vivo measures of a limited set of brain metabolites, and aspects of AD neuropathology have long been associated with consistent changes in certain metabolites within its sensitivity. Specifically, reductions in the neuronal marker N‐Acetyl Aspartate (NAA) have long been associated with neurodegeneration, and elevations in myo‐inositol (mI), have been associated with reactive astrocytosis 14, 17, 18. Despite its immediate relevance to metabolic dysfunction, glucose has rarely been mentioned in earlier MRS studies.…”
Section: Introductionmentioning
confidence: 99%